Expression Profile of Tyrosine Phosphatases in HER2 Breast Cancer Cells and Tumors - Maria Antonietta Lucci; Rosaria Orlandi; Tiziana Triulzi; Elda Tagliabue; Andrea Balsari; Emma Villa-Moruzzi (Cellular Oncology)
Background: HER2-overexpression promotes malignancy by modulating signalling molecules, which include PTPs/DSPs (protein tyrosine and dual-specificity phosphatases). Our aim was to identify PTPs/DSPs displaying HER2-associated expression alterations.